Analisis Strategi Promosi Jasa Makeup Artist Pemula melalui Media Sosial Mahasiswi Tata Rias dan Kecantikan - Indriyani, Adinda; Rahmiati, Rahmiati; Hayatunnufus, Hayatunnufus; Oktarina, Rahmi (Lembaga Yasin AlSys, 2025)
Beginner makeup artists (MUAs) from beauty and cosmetology programs are expected to implement effective promotional strategies through social media, although its utilization is often suboptimal. This study aims to analyze the promotional strategies of beginner MUAs on social media, focusing on the promotion mix (advertising), the effectiveness of Instagram, and the use of WhatsApp. A quantitative survey method was applied to 75 respondents who had previously used MUA services, with data collected through a questionnaire tested for validity and reliability. The results indicate that advertising-based promotional strategies are considered moderately effective, with Instagram emerging as the most dominant and effective platform due to its feed, story, reels, and caption features that support visual promotion. Meanwhile, WhatsApp is predominantly used for personal communication and remains underutilized for visual promotion. The study concludes that beginner MUAs’ promotional strategies on social media have been reasonably successful, particularly through Instagram, and recommends enhancing creativity and consistency in social media use, alongside optimizing WhatsApp to support comprehensive service promotion.